User Preferences on Supplementary Learning Tool in Physics Experiment Using Mobile AR - Gopalan, Valaramthie; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (2018)
Mobile augmented reality (AR) technology is utilized as the medium for enhancing real time interaction between user and technology by adding virtual contents to the real world. However, this technology is about to grow in the learning landscape. The focus of this article is to determine user preferences on technology based supplementary learning tool in Physics experiment. In this study, a user requirement is conducted by means of questionnaire. This questionnaire was distributed among target group and school teachers. Findings of user requirements provide evidence on the necessity and potentials of Mobile AR to be used as a supplementary learning tool. This exercise provides details on the learning content and technology they would like to acquire.